Non-motor Symptom Burden and Its Clinical Correlates in Parkinson’s Disease: A Cross-sectional Study in Indonesia - Situmeang, Rocksy Fransisca V; Gabriella, Nadia (Jurnal Kedokteran Meditek, 2026)
Introduction: Non-motor symptoms (NMS) are increasingly recognized to have disabling impact on the quality of life of idiopathic Parkinson’s disease (PD) patients, comparable to motor symptoms. However, their relationship with clinical and demographic factors remains obscure in local populations. Purpose: To determine the prevalence of NMS in idiopathic PD and evaluate their correlation with clinical variables, including disease duration, Hoehn & Yahr (H&Y) stage, and PD subtype. Methods: This cross-sectional study consecutively included idiopathic PD subjects evaluated between July-October 2025. Data collected included age, gender, age at onset, disease duration, H&Y stage, and PD subtype. NMS were assessed using the Indonesian version of Non-Motor Symptoms Questionnaire (NMS-Q). Correlation and multiple linear regression analyses performed. Results: Fifty-three subjects were included (mean age 66.9±10.5 years; 50.9% male). Median disease duration was 5 years (IQR 1–7.5), with majority in H&Y stage 2 (49%). Mean total NMS-Q score was 10.7±5.2. The most frequent NMS was urinary urgency (66%), with urinary domain being the most affected (64.2%). Total NMS-Q scores correlated with H&Y stage (r=0.427, p=0.001) and disease duration (r=0.309, p=0.025). Only H&Y stage independently predicted total NMS-Q scores (B=2.657, p=0.010). Conclusion: This study provides additional evidence from an Indonesian population using a standardized assessment tool, demonstrating that disease severity is an independent predictor of NMS burden, thus highlighting the importance of early and systematic evaluation of NMS in idiopathic PD.